The role of university administration in spreading the entrepreneurship culture among students of Prince Satam bin Abdulaziz University and the obstacles to activating it from the viewpoint of the university administration - Al-Dosari, Amal Farhan Nasser; Al-Saqer, AbdulAziz Muhammad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the role of university administration in promoting entrepreneurship culture among Prince Sattam bin Abdulaziz University students, as well as to identify the main obstacles that hinder its effectiveness. The study adopted a descriptive methodology with both documentary and survey techniques. A questionnaire was distributed to a purposive sample of 140 administrative and academic leaders at the university. The study found several results, including that the university administration largely agrees with the obstacles that hinder its role in promoting entrepreneurship culture among students, with an overall average of 3.78 out of 5. The obstacles were ranked as follows in terms of their overall averages: material (4.03), organizational (3.96), societal (3.95), human (3.82), educational (3.79), and finally, student activities (3.12), which had a moderate rating. The results also showed a large degree of agreement on the need to identify the requirements for activating the role of university administration in promoting entrepreneurship culture among students. Based on the study’s results, the study recommended several recommendations, the most important of which were: the need for the university management to prepare a clear, measurable, and applicable implementation plan for disseminating an entrepreneurial culture among students. Additionally, the study recommended integrating entrepreneurial education into the university curricula for all scientific specialties. The study also recommended that the university management implement a number of media activities and guidance events that promote entrepreneurship among students.